2002
DOI: 10.1071/pp01184
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of inorganic carbon acquisition mechanisms in eukaryotic microalgae

Abstract: Eukaryotic microalgae have developed CO2concentrating mechanisms to maximise the concentration of CO2 at the active site of Rubisco in response to the low CO2 concentrations in the external aquatic medium. In these organisms, the modes of inorganic carbon (Ci) uptake are diverse, ranging from diffusive CO2 uptake to the active transport of HCO3 -and CO2 and many have an external carbonic anhydrase to facilitate HCO3- use. There is unequivocal evidence for the mechanisms of Ci uptake in only about 25 species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
118
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(122 citation statements)
references
References 56 publications
3
118
0
1
Order By: Relevance
“…The α and F v /F m increased with increasing CO 2 , indicating that the efficiency of light-harvesting and energy conversion in photosynthesis were increased. Down-regulation of Rubisco and inorganic carbon concentrating mechanisms (CCM) activities has been reported in many species (Wong 1979;Vu et al 1983;Bowes 1993;Colman 2002;Matsuda et al 2002). The present study indicated that the apparent carboxylating efficiency and the photosynthetic affinity for CO 2 markedly decreased under elevated CO 2 in S. costatum, suggesting that the similar down-regulation of Rubisco and CCM activities may also exist in this alga.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The α and F v /F m increased with increasing CO 2 , indicating that the efficiency of light-harvesting and energy conversion in photosynthesis were increased. Down-regulation of Rubisco and inorganic carbon concentrating mechanisms (CCM) activities has been reported in many species (Wong 1979;Vu et al 1983;Bowes 1993;Colman 2002;Matsuda et al 2002). The present study indicated that the apparent carboxylating efficiency and the photosynthetic affinity for CO 2 markedly decreased under elevated CO 2 in S. costatum, suggesting that the similar down-regulation of Rubisco and CCM activities may also exist in this alga.…”
Section: Discussionsupporting
confidence: 49%
“…The photosynthetic affinity for CO 2 and carbonic anhydrase activity in many microalgae declines with CO 2 enrichment (Bowes 1993;Matsuda et al . 2002;Colman et al . 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The subcellular location and function of these components have been extensively studied in cyanobacteria and microalgae (see Colman et al 2002 andBadger 2003, for recent reviews). In all cases, internal carbonic anhydrase (CA) seems to be an essential component of the CCMs.…”
Section: Introductionmentioning
confidence: 99%
“…(c) Algae There is apparently greater diversity of CCMs in algae than in cyanobacteria (table 1c-g,i ) and less is known about the mechanisms and molecular genetics of the CCMs (Badger et al 1998;Colman et al 2002;Giordano et al 2005). Pyrenoids, which are within the chloroplast stroma and contain rubisco, occur in many algae expressing CCMs.…”
Section: The Range Of Organisms With Ccms (A) Backgroundmentioning
confidence: 99%
“…CCMs occur today in all the cyanobacteria examined, in all algae apart from a few members of the Chlorophyta and Rhodophyta as well as most or all members of the Chrysophyceae and Synurophyceae, as well as in some hornworts, lycopsids and ferns, and in a significant number of flowering plants ( Winter & Smith 1995;Badger et al 1998Badger et al , 2002Sage & Monson 1998;Colman et al 2002;Keeley & Rundel 2003;Price & Badger 2003;Edwards et al 2004;Giordano et al 2005;Raven et al 2005a-c;Price et al 2007;Roberts et al 2007a,b; (b) Cyanobacteria In cyanobacteria, the CCM is based on accumulation of HCO K 3 in the cytosol (table 1a,b), movement of this HCO K 3 through their proteinaceous shells into the carboxysomes containing rubisco, and conversion to CO 2 using one or more carbonic anhydrase (CA) enzymes (Badger et al 2002;Price et al 2007). The open ocean cyanobacteria with form IA rubiscos have a restricted suite of HCO K 3 accumulation processes and, probably, little capacity to acclimatize to decreased inorganic C availability (an unlikely event in the pelagic ocean).…”
Section: The Range Of Organisms With Ccms (A) Backgroundmentioning
confidence: 99%